Electroretinography in adults with high‐functioning autism spectrum disorder. Issue 11 (10th October 2022) - Friedel, Evelyn B. N.; Schäfer, Mirjam; Endres, Dominique; Maier, Simon; Runge, Kimon; Bach, Michael; Heinrich, Sven P.; Ebert, Dieter; Domschke, Katharina; Tebartz van Elst, Ludger; Nickel, Kathrin
Abstract: The electroretinogram (ERG) allows the investigation of retinal signaling pathways and has increasingly been applied in individuals with mental disorders in search for potential biomarkers of neurodevelopmental disorders. Preceding ERG examinations in individuals with autism spectrum disorders (ASD) showed inconsistent results, which might be due to the small number of participants, heterogeneity of the ASD population, differences in age ranges, and stimulation methods. The aim of this study was to investigate functional retinal responses in adults with ASD by means of the light‐adapted (photopic) ERG. Light‐adapted ERG measurements were obtained with the RETeval® system applying three different stimulation protocols. In the final analysis, the ERG parameters a‐wave, b‐wave, the photopic negative response (PhNR), the photopic hill parameters as well as additional amplitude ratios were compared between 32 adults with high‐functioning ASD and 31 non‐autistic controls. Both groups were matched with regard to sex and age. No significant functional retinal differences in amplitude or peak time of the a‐ or b‐wave, PhNR, the photopic hill parameters or the ERG‐amplitude ratios could be detected in individuals with ASD compared to non‐autistic participants. The absence of electrophysiological functional retinal alterations in ASD, suggests that changes in visual perception, such as increased attention to detail or visual hypersensitivity in ASD, are not due to impairments at early levels of retinal signal processing. Lay Summary: The electroretinogram (ERG), an ophthalmologic method to assess the integrity of retinal functioning, was investigated in individuals with autism spectrum disorder compared to non‐autistic controls. Individuals with autism spectrum disorder showed normal ERG parameters when compared to non‐autistic controls. These results suggest that changes in the visual perception or visual hypersensitivity in autism spectrum disorder are not due to dysfunctions at early levels of retinal signal processing.